POTENSI BERPIKIR KREATIF SISWA DALAM MATERI BILANGAN DIKAJI DARI SELF CONFIDENCE DI SMP - Dewi Meylisa; Sugiatno Sugiatno; Dian Dian (Universitas Tanjungpura, 2020)
AbstractThis study aimed to exploit the creative potential of students in numeric assignments assessed from the self-confidence a students. This type of research was descriptive research. The subjects in this study involved 9 junior high school students. The object of this research was the potential for creative thinking of students in material assignments that are reviewed from self-confidence. The data aids used were creativity tests, questionnaires, and interviews. An analytic framework to expose the potential for creative thinking using “The Torrance Tests of Creative Thinking (TTCT)”. While the data analysis technique used qualitative data analysis by Miles and Huberman method. The test results obtained are from 9 students, there were 4 students who are in high self-confidence who have the ability to think mathematically creative